Urban Squares within the Framework of Urban Design: Kadıköy Square, Turkey - Altay, Elvan Ender; Batman, Zeynep Pirselimoğlu; Acaray, Sevil Canbolat (Landscape Architecture and Art, 2023)
This article aims to give a comprehensive perspective to the design concept in urban squares, which is the research subject of landscape architecture and related disciplines, and to reveal the criteria in the design process. This research was carried out with the idea of "how to design urban squares as a qualified urban service area?". For the squares to fulfill their functions and be well-functioning urban services, they should be evaluated in the light of various design criteria. In this study, using AHP (Analytical Hierarchy Process), 40 different design criteria were brought together and examined in Kadıköy square in Istanbul. In this context, a multi-criteria design approach has been developed that will enable citizens to spend more of their free time in the squares and to adopt positive feelings in these spaces. By evaluating the research criteria, it was found that 21 criteria were not included in the design process in Kadıköy Square. For this reason, Kadıköy Square is in a low suitability class. The study is seen as a mechanism that shows the unique features of urban squares in the design process and how the squares should be developed in the process of becoming a qualified service area. While studies are emphasizing that the squares in the cities are important open spaces, there are no studies that include concrete criteria that can ensure that the squares are qualified spaces. Bringing together all the criteria related to squares and creating a basis for a multi-criteria design process reveals the value of the study.